Tricin attenuates cerebral ischemia/reperfusion injury through inhibiting nerve cell autophagy, apoptosis and inflammation by regulating the PI3K/Akt pathway. (2nd September 2022) - Liu, Ying; Qu, Xiaoning; Yan, Mengjun; Li, Dalei; Zou, Rong
To elucidate the effect of tricin in cerebral ischemia/reperfusion (I/R) injury and examine its possible underlying mechanisms. Rats were randomly divided into Sham (exposed the right internal carotid arteries), I/R, and tricin (administered at various doses) groups. After the cerebral I/R injury model was established, a Morris water maze test and a tetrazolium chloride assay were performed. Apoptosis and autophagy were assessed in the nerve cells of hippocampus tissue, and the levels of inflammatory markers within animal serum were detected. Proteins related to apoptosis and the PI3K/Akt pathway were evaluated. To further investigate the mechanisms by which tricin affects brain damage, mouse neuroblastoma cells N2a were divided into control, oxygen-glucose deprivation and reoxygenation (OGD/R), tricin, PI3K/Akt activator, and tricin + PI3K/Akt inhibitor groups. The cell viability, apoptosis, inflammatory factors, and PI3K/Akt pathway related proteins in N2a cells were also detected. The results revealed that I/R-induced learning and memory dysfunction was improved by tricin treatment. The area of cerebral infarction, the levels of apoptosis and autophagy in nerve cells, and the serum inflammatory marker content were all decreased following tricin treatment. Additionally, the expression of Beclin-1 protein was downregulated, while the expression of Bcl-2 protein, p-PI3K/PI3K and p-Akt/Akt was upregulated after tricin treatment. Mechanistically, tricin or PI3K/Akt activator ameliorated OGD/R-induced apoptosis, autophagy, and inflammation. However, these effects were reversed following PI3K/Akt inhibitor treatment in OGD/R-induced N2a cells. In summary, this study suggested that tricin can against I/R-induced brain injury by inhibiting autophagy, apoptosis and inflammation, and activating the PI3K/Akt signaling pathway.